Thymic cyst: About a case - Croci, Fabio; Martínez, José Luis; Gastambide, Carmelo; Arce, Enrique (Cirugía del Uruguay, 1982)
The authors present a case of thymic cyst. It is a lesion of very low incidence, of congenital origin, that can be found at any age, it has a medlastinal topography, usually having a close relation with the great vessels and the heart base. They are generally asymptomatic, but they can grow rapidly due to hemorrage, inflamation or its becoming malignant. They can present the symptoms of an acute mediastinal syndrome. The clinical diagnosis is difficult and can only be suspected for its radiological characteristics. Its trestment consists of surgical resection.